Iota-Carrageenan/Chitosan Nanoparticles via Coacervation: Achieving Stability for Tiny Particles - Rosecler S. Klein; Débora A. de Almeida; Ariel C. de Oliveira; Elton G. Bonafé; Johny P. Monteiro; Roberta M. Sabino; Alessandro F. Martins (Nanomaterials, 2025)
This study investigated the influence of parameters such as pH condition, polyelectrolyte concentration, polymer ratio, and order of addition of the commercial polyelectrolytes chitosan and iota-carrageenan (ι-carrageenan) on the formation of polymeric nanoparticles in suspension (coacervates). A preliminary purification step of the polymers was essential for obtaining stable nanoparticles with small sizes as impurities, particularly metal ions that interfere with complexation, are removed by dialysis. Microparticles (13.5 μm in dry diameter) are obtained when aliquots of chitosan solution are poured into the ι-carrageenan solution. In general, an excess of chitosan results in the formation of agglomerated particles. The addition of an aliquot of ι-carrageenan solution (30 mL at 0.6 mg/mL and pH 4.0) to the chitosan solution (6.0 mL at 0.3 mg/mL and pH 4.0) leads to dispersed nanoparticles with a hydrodynamic radius of 278 ± 5 nm, a zeta potential of −31 ± 3 mV, and an average dry diameter of 45 ± 11 nm. The hydrodynamic radius increases as the pH rises. The partial deprotonation of ι-carrageenan chains enhances the interaction with water molecules, causing the particles to swell. These findings contribute to the fundamental understanding of polyelectrolyte complexation processes in aqueous suspension and provide insights for developing stable nanomaterials for potential practical applications.